Abortion care at 20 weeks and over in Victoria: a thematic analysis of healthcare providers' experiences - Mary Malek; Caroline SE Homer; Clare McDonald; Catherine M Hannon; Paddy Moore; Alyce N Wilson (BMC, 2024)
Abstract Background In many countries, abortions at 20 weeks and over for indications other than fetal or maternal medicine are difficult to access due to legal restrictions and limited availability of services. The Abortion and Contraception Service at the Royal Women's Hospital in Victoria, Australia is the only service in the state that provides this service. The views and experiences of these abortion providers can give insight into the experiences of staff and women and the abortion system accessibility. The aim of this study was to examine health providers' perceptions and experiences of providing abortion care at 20 weeks and over for indications other than fetal or maternal medicine, as well as enablers and barriers to this care and how quality of care could be improved in one hospital in Victoria, Australia. Methods A qualitative study was conducted at the Abortion and Contraception Service at the Royal Women's Hospital. Participants were recruited by convenience and purposive sampling. Semi-structured interviews were conducted one-on-one with participants either online or in-person. A reflexive thematic analysis was performed. Results In total, 17 healthcare providers from medicine, nursing, midwifery, social work and Aboriginal clinical health backgrounds participated in the study. Ultimately, three themes were identified: 'Being committed to quality care: taking a holistic approach', 'Surmounting challenges: being an abortion provider is difficult', and 'Meeting external roadblocks: deficiencies in the wider healthcare system'. Participants felt well-supported by their team to provide person-centred and holistic care, while facing the emotional and ethical challenges of their role. The limited abortion workforce capacity in the wider healthcare system was perceived to compromise equitable access to care. Conclusions Providers of abortion at 20 weeks and over for non-medicalised indications encounter systemic enablers and barriers to delivering care at personal, service delivery and healthcare levels. There is an urgent need for supportive policies and frameworks to strengthen and support the abortion provider workforce and expand provision of affordable, acceptable and accessible abortions at 20 weeks and over in Victoria and in Australia more broadly.